Reduction of Insulin Signaling Upregulates Angiopoietin-like Protein 4 Through Elevated Free Fatty Acids in Diabetic Mice - Mizutani, N.; Ozaki, N.; Seino, Y.; Fukami, A.; Sakamoto, E.; Fukuyama, T.; Sugimura, Y.; Nagasaki, H.; Arima, H.; Oiso, Y. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Angiopoietin-like protein 4 (Angptl4) is thought to cause an increase in serum triglyceride levels. In the present study, we elucidated Angptl4 expression in the mouse models of type 1 and type 2 diabetes mellitus, and investigated the possible mechanisms involved.Type 1 diabetes was induced in C57BL/6 J mice by treating them with streptozotocin (STZ). Type 2 diabetes was induced by feeding the mice a high-fat diet (HFD) for 18 weeks.The levels of Angptl4 mRNA expression in liver, white adipose tissue (WAT), and brown adipose tissue (BAT) were found to increase in the STZ diabetic mice relative to control mice. This effect was attenuated by insulin administration. In the HFD diabetic mice, the Angptl4 mRNA expression levels were increased in liver, WAT, and BAT. Treatment with metformin for 4 weeks attenuated the increased levels of Angptl4 mRNA. Fatty acids (FAs) such as palmitate and linoleate induced Angptl4 mRNA expression in H4IIE hepatoma cells and 3T3-L1 adipocytes. Treatment with insulin but not metformin attenuated FA-induced Angptl4 mRNA expression in H4IIE. Both insulin and metformin did not influence the effect of FAs in 3T3-L1 cells.These observations demonstrated that Angptl4 mRNA expression was increased through the elevated free FAs in diabetic mice.
Keywords: diabetes mellitus; fatty acids; insulin